Authenticity across languages and cultures themes of identity in foreign language teaching and learning - Will, Leo 1983-; Stadler, Wolfgang; Eloff, Irma (Second language acquisition, 2023)
This volume centres around concepts of personal and cultural authenticity in foreign language teaching and learning. The chapters cover a wide range of contexts and disciplines, offering diverse perspectives regarding the role language plays in processes of personal growth, self-actualization and power struggles